LEGAL RECONSTRUCTION FOR AUTONOMOUS VEHICLE USE IN INDONESIA: CHALLENGES AND SOLUTIONS IN THE AGE OF ARTIFICIAL INTELLIGENCE - Djohan, Naufal Hasanuddin; Indarti, Erlyn; Malik, Muhammad Fahad (Faculty of Law, Universitas Diponegoro, 2025)
This research explores the urgent need for a legal framework governing the use of Autonomous Vehicles (AVs) in Indonesia, focusing on the integration of Artificial Intelligence (AI) technologies in transportation. With traffic accidents accounting for a significant portion of global fatalities, the adoption of AVs powered by AI is seen as a potential solution to reduce human errors and enhance road safety. However, Indonesia’s existing traffic laws, primarily focused on conventional vehicles, lack provisions for AVs, creating a legal vacuum. This study compares the legal structures of AVs in the United Kingdom and Indonesia, highlighting the differences in recognition, liability, and regulation. Drawing on the concept of